Adaptasi Proses Pembelajaran Bahasa Asing Pada Konteks Pemanfaatan TIK - Tamtomo, Tomi (STBA Yapari-ABA Bandung, 2011)
The fact that ownership and usage of some ICT-based electronic devices have been so widespread should not be ignored by the teaching of foreign languages, especially ESL. Some subjects of English teaching can make the most of some computer / Internet applications that have been previously popular, such as Facebook, Twitter, Yahoo Messenger, Blogging Platforms, and so on. The ways that those applications could be integrated in the process of ESL teaching is described and whether the integration could conform to the norms of effectiveness of application (PICCA) is analyzed.